Effect of Neem (Azadirachta Indica) on Fertility in Male Rats - Khan, Asma; Begum, Zinnat Ara; Khan, Md Ismail; Rahman, Hasanur; Banu, Layla Afroza (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Azadirachta indica locally known as neem has been claimed to possess antifertility properties by many investigators. Objective: The present study was designed to evaluate the antifertility effect of Azadirachta indica leaf powder in male rats. Methodology: The study was carried out in pharmacology and Therapeutic Department of Dhaka Medical College during the period of January 2008 to December 2008. Total number of 24 rats was divided into 4 groups. Group A was served as control, group B, C and D were treated by Azadirachta indica leaf powder orally, inj. testosterone I/M, & Azadirachta indica leaf powder orally, inj. testosterone I/M respectively for 48 days. They were sacrificed on 49 day. Then morphological and histological study was done. Result: The result showed that the all of the Azadirachta indica leaf powder treated rats has significant antispermatognic effect as well as antiandrogenic effect. Conclusion: The Azadirachta indica leaf powder reduced motility and density of sperm and causes structural changes of leydig cells and seminiferous tubule. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16206 J Shaheed Suhrawardy Med Coll, 2013;5(1):39-42